A study on the effectiveness of promotional strategies towards increasing occupancy rate at the Saujana, Kuala Lumpur - Asri, Ashfaq Farhan (2006)
Promotion is very important to many organizations. A good promotion may promise a good feedback from the customers towards the products and services offered. This project paper is to assess promotion strategies done by The Saujana, Kuala Lumpur. The objective of this research is to identify the effectiveness of promotional strategies by The Saujana in promoting their products and services and to find out customer awareness towards The Saujana products and services. In getting relevant data, 100 questionnaires were distributed to the selected respondents. The respondents are potential customer of The Saujana at Kuala Lumpur and Klang Valley area. Data collected were analyzed by using Statistical Package for Social Science (SPSS) program. The analysis includes the frequency, and cross-tabulation. Several limitations were faced in completing in this study. The sampling size is small compared to actual populations of The Saujana customers. Therefore, to obtain the correct sample size may required more times and effort which is beyond researcher capabilities and time frame given. Thus, recommendations are included in this project paper in order to help The Saujana to increase the effectiveness of the promotions strategies and create customers awareness towards the products and services.